Web based calculator for GeSiSn semiconductor band parameters - Htet, Myo Oo (2019)
Elemental semiconductor band parameters such as lattice constant, band gap and inter-band values are published and readily available in the literature. However, calculation of band parameters for compound semiconductor can be tedious due to the existence of bowing parameter and temperature-dependent parameters. Therefore, deep understanding of the subject matter is required in order to calculate the band parameters accurately. The primary objective of this project is to develop a web based application for the calculation of Group IV compound semiconductors’ band parameters. As a secondary function, users will be able to download the result as text file for future reference. The implementation is through the use of web development tools such as JavaScript, CSS, HTML, JSP and Servlet. Integrated Development tool used in this project is Eclipse. Tomcat Server developed by the Apache Software Foundation is used as a Java Servlet Container. Hosting the web application is done in cloud computing platform offered by Amazon Web Services.